REKONSTRUKSI RELASI IKHTIAR DAN TAKDIR DALAM NOVEL SANG ALKEMIS MELALUI KONSEP KASB AL-GHAZALI: PEMBACAAN HERMENEUTIKA GADAMER–RICOEUR ATAS PERJALANAN EKSISTENSIAL SANTIAGO - Fiki Nursanti; Zainuddin Fanani (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2026)
The growing popularity of spiritual trends such as manifesting and the law of attraction has revived philosophical debates concerning the relationship between human agency (ikhtiar) and divine destiny (takdir). Meanwhile, scholarly discussions of Paulo Coelho's The Alchemist have largely emphasized symbolic and humanistic perspectives, leaving its interpretation within the framework of Islamic theology relatively unexplored. This study aims to reinterpret the relationship between ikhtiar and takdir in the novel through Al-Ghazali's concept of kasb. Employing a qualitative library research approach, the study uses The Alchemist as the primary source, while Al-Ghazali's works and scholarly publications indexed in SINTA and Scopus serve as secondary sources. Data were analyzed by integrating the philosophical hermeneutics of Gadamer and Ricoeur with the conceptual framework of kasb. The findings indicate that Santiago's actions represent kasb as a form of human endeavor that remains subject to divine will. Furthermore, the concept of Maktub undergoes a contextual transformation from its Arab-Islamic theological horizon into global popular literature through the process of fusion of horizons. The study proposes the Ikhtiar–Kasb–Qudrah Hadithah–Maktub–Takdir–Existence model and introduces Kasb Hermeneutics as a novel interpretative approach for cross-cultural literary studies.